2016
DOI: 10.1007/s12013-016-0736-7
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid Inhibits High Salt-Induced Exaggeration of Warburg-like Metabolism in Breast Cancer Cells

Abstract: Cancer cells have a proliferative advantage by utilizing intermediates of aerobic glycolysis (Warburg-effect) for their macromolecule synthesis. Although the exact causes of this Warburg-effect are unclear, high osmotic stress in solid tumor microenvironment is considered as one of the important factors. Oleanolic acid (OA) is known to exert anti-inflammatory and anti-cancer effect. In our current studies, using breast cancer cell lines, we determined the protective role of OA in high salt mediated osmotic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 28 publications
3
41
1
Order By: Relevance
“…Masui et al have recently demonstrated that mTORC2 enhances Warburg-like glucose metabolism and drug resistance in cancer cells [33]. Previous studies from our lab have demonstrated that high salt enhances Warburg-like metabolism in cancer cells [13]. Our current studies along with previous observations potential suggest a mTORC2/ SIK3 cascade plays an important role in Warburg metabolism and enhances cancer proliferations.…”
Section: Discussionsupporting
confidence: 75%
“…Masui et al have recently demonstrated that mTORC2 enhances Warburg-like glucose metabolism and drug resistance in cancer cells [33]. Previous studies from our lab have demonstrated that high salt enhances Warburg-like metabolism in cancer cells [13]. Our current studies along with previous observations potential suggest a mTORC2/ SIK3 cascade plays an important role in Warburg metabolism and enhances cancer proliferations.…”
Section: Discussionsupporting
confidence: 75%
“…This study suggested that oleanolic acid can cause apoptosis through mitochondrial-related pathways promoting the release of mitochondrial-associated caspases and pro-apoptotic Bax proteins [91]. In addition, oleanolic acid inhibited aerobic glycolysis by inducing pyruvate kinase muscle (PKM)isoforms switch from PKM2 to PKM1 through suppression of phosphorylated mTOR, consequently disrupting Warburg effects in various cancer cells [92].…”
Section: Oleanolic Acid As Anticancer Agentmentioning
confidence: 99%
“…We have previously demonstrated that high salt (Δ0.05 M NaCl) synergized with subminimal IL-17 (0.1 pg/ml) (16) to induce a 24% enhanced cell proliferation (4,5,8,22), which will be referred to as stimulating conditions in our current communication. Importantly, Na-MRI based human studies have revealed that breast tumors accumulate high salt for yet unknown reasons (6,7).…”
Section: Enhanced Cytotoxic Effect Of Prostratin On Breast Cancer Celmentioning
confidence: 93%
“…For salt and interleukin-17 treatment conditions, cell culture media was supplemented with 0.05 M NaCl (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) and 0.1 ng/ml IL-17 (Thermo Fisher Scientific, Inc.). We have previously performed a dose-response for salt (0-0.1 M NaCl) and IL-17 (0-1,000 ng/ ml) and found-out that 0.05 M NaCl provided highest cell proliferation (4,5) and 0.1 ng/ml of IL-17 induced sub-effective inflammatory cytokine response (4,16). All chemicals unless mentioned were obtained either from Sigma-Aldrich; Merck KGaA (Darmstadt, Germany) or Thermo Fisher Scientific, Inc. For siRNA knock down of SIK3 we have used the following two siRNA sequences: SIK3-siRNA-1: 5'-GUG CAG AGU GUU GGA GUC C-3'; scramble SIK3-siRNA-1: 5'-UGG AGG CGA GUC AGU UUG C-3' .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation